2017
DOI: 10.3168/jds.2016-12376
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of putative sex pheromone components during heat periods in estrus-induced cows

Abstract: Determination of the optimal insemination time in dairy cows is vital for fertilization success and is a challenging task due to silent or weak signs of estrus shown by some cows. This can be overcome by combining several estrus detection methods, leading to higher detection rates. However, an efficient, noninvasive method for detecting estrus in cows is still needed. Chemical cues released by the cow during estrus have been proposed to have pheromonal properties and signal readiness to mate to the bull. Such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A recent study shows that acetic, valeric, caproic and myristoleic acids are at signi cantly higher levels in the milk of estrus cow (Zebari et al 2019). The fatty acids, acetic and propanoic, have been identi ed in the faeces of cow, and varied in relation to the time of ovulation (Mozūraitis et al 2017). The present investigation supports the previous reports of presence of acetic, propanoic and valeric acids as produced by CVM bacteria in estrus buffalo.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that acetic, valeric, caproic and myristoleic acids are at signi cantly higher levels in the milk of estrus cow (Zebari et al 2019). The fatty acids, acetic and propanoic, have been identi ed in the faeces of cow, and varied in relation to the time of ovulation (Mozūraitis et al 2017). The present investigation supports the previous reports of presence of acetic, propanoic and valeric acids as produced by CVM bacteria in estrus buffalo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that acetic acid, propionic acid, and 1-iodoundecane are present in bovine feces specifically at estrus, and application to the genital region of diestrous cows stimulated mounting behavior and the Flehmen response in bulls (Sankar and Archunan, 2004). Changes in acetic and propionic acid in feces relative to the time of ovulation have also been described (Mozūraitis et al, 2017). Interestingly, animals with a highly developed olfactory system are also able to detect estrus in cows.…”
Section: Introductionmentioning
confidence: 97%
“…Bulls exhibit this behavior in response to the presence of a mixture of volatile pheromones present in female excretions (Sankar and Archunan, 2004). Not only mucus but also urine and feces can be a source of volatile organic compounds (VOC) associated with estrus (Le Mozūraitis et al, 2017;Ramachandran et al, 2020). It has been reported that acetic acid, propionic acid, and 1-iodoundecane are present in bovine feces specifically at estrus, and application to the genital region of diestrous cows stimulated mounting behavior and the Flehmen response in bulls (Sankar and Archunan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A significant relationship between pheromones and reproductive hormones in pigs [ 10 ] and Asian elephants [ 11 ] was observed. Furthermore, pheromones are known to have a direct influence on various behavioral activities during the estrus cycle in gray opossums [ 12 ], Asian elephants [ 11 , 13 ], sows [ 14 ], blackbuck [ 15 ], mice [ 16 ], and bovine [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%